Medidas Sostenibles para el desarrollo Urbano - Creación de entornos sostenibles, justos y equitativos - González Paredes, Geovanna Del Carmen (2024)
The urban growth without adequate territorial planning can lead to a lack of access to basic services, where poor land organization results in uncontrolled settlement expansion and insufficient coverage of essential infrastructure. The study of territorial planning is conducted using ArcGIS to perform a detailed spatial analysis that illustrates soil capacity, mining zones, and human settlements, with the aim of identifying vulnerable areas. The research also addresses the impact of current laws, such as the Organic Law of Territorial Planning, Use, and Management of Land (LOOTUGS) and the Organic Code of Territorial Organization, Autonomies, and Decentralization (COOTAD), on territorial planning and management. Furthermore, it proposes a reform to COOTAD to ensure the active participation of civil society, non-governmental organizations, academic institutions, and the private sector in the development of Territorial Development and Planning Plans (PDTO). The goal is to analyze the application of environmental regulations in urbanization processes to create sustainable, fair, and equitable environments in Ecuador. The research aims to contribute to a better understanding of territorial planning and support sustainable and effective planning in Ecuador."